The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/mao.0b013e3182382a7c
|View full text |Cite
|
Sign up to set email alerts
|

Electrocochleography as a Diagnostic and Intraoperative Adjunct in Superior Semicircular Canal Dehiscence Syndrome

Abstract: These findings expand the differential diagnosis of abnormal ECoG. In conjunction with clinical findings, ECoG may support a clinical diagnosis of SSCD. Intraoperative ECoG facilitates dehiscence documentation and allows the surgeon to confirm satisfactory canal occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 24 publications
(32 reference statements)
4
40
0
Order By: Relevance
“…Predictive value of SP/AP for determining endolymphatic hydrops in Meniere's disease varies ranging from 0.3 to 0.5 Coats, 1986;Goin et al, 1982). Recently, an elevated SP/AP ratio has been reported in patients with SCD (Adams et al, 2011;Arts et al, 2009). However, few studies have addressed ECoG findings in patients with SCD syndrome and its diagnostic value has not compared to that of Meniere's disease.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Predictive value of SP/AP for determining endolymphatic hydrops in Meniere's disease varies ranging from 0.3 to 0.5 Coats, 1986;Goin et al, 1982). Recently, an elevated SP/AP ratio has been reported in patients with SCD (Adams et al, 2011;Arts et al, 2009). However, few studies have addressed ECoG findings in patients with SCD syndrome and its diagnostic value has not compared to that of Meniere's disease.…”
Section: Discussionmentioning
confidence: 95%
“…SP to AP ratio was also elevated in patients with SCD (Adams et al, 2011;Arts et al, 2009). In these previous studies, ECoG monitoring showed that ears with SCD had significantly higher SP/AP ratios and these ratios decreased after surgical correction, and thus, it was concluded that ECoG may support a clinical diagnosis of SCD (Adams et al, 2011;Arts et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Further concern about the test specificity has been raised by a study showing that superior semicircular dehiscence syndrome (SSCD) gives similarly raised thresholds [7]. SSCD has the ability to mimic MD by causing episodic vertigo, and asymmetrical hearing loss.…”
Section: Electronystagmographymentioning
confidence: 99%
“…The study failed to show a statistically significant difference in the percentage of raised summation potentials between the definite and non-definite groups. Additionally, over 30% of those with definite MD would not have been classified as having MD based on ECoG results alone [6].Further concern about the test specificity has been raised by a study showing that superior semicircular dehiscence syndrome (SSCD) gives similarly raised thresholds [7]. SSCD has the ability to mimic MD by causing episodic vertigo, and asymmetrical hearing loss.…”
mentioning
confidence: 99%